Establishing a mental health system in the Occupied Palestinian Territories - Giacaman, Rita (Int Psychiatry, 2005)
What is ‘mental health’ during the societal crisis and upheaval occasioned by war? Perhaps the primary psychological effect of war on victims generally is through their witnessing the destruction of a social world embodying their history, identity, values and roles of everyday life. Such suffering has largely to be resolved collectively, in this same social world, albeit one which has been intentionally weakened. Thus, as the World Health Organization and other authorities confirm, the major thrust of humanitarian interventions must be towards the depleted social fabric and its institutions, for herein lie the sources of resilience and capacity for recovery for all (Kawachi & Berkman, 2000). Beyond that, history has shown that social or political reform is the best medicine, and for victims of oppressive violence this means acknowledgement and justice (Summerfield, 2002).